DEVELOPMENT OF A PROJECT-BASED LEARNING INTERACTIVE E-MODULE FOR BASIC AUTOMOTIVE COURSES AT SMK NEGERI 2 MEDAN - Marbun, Samuel; Daryanto, Eka (Yayasan Amanah Nur Aman, 2025)
The development of learning media is highly demanded in the world of education, especially by utilizing increasingly sophisticated technology. This research produces e-learning modules using a valid, practical flip PDF application in Basic Automotive subjects. This research development model uses ADDIE (Analysis, Design, Development, Implementation, Evaluation). This research was conducted at SMK Negeri 2 Medan in class X with 36 respondents. Validation of media experts with an average of 93.75%, validation of design experts with an average of 95.50%, material expert validation with an average of 95.75% so that the media is very feasible to be tested. The teacher's response to the media is 92.00% and the student's response is 90.75%. So that it can be, the classical completeness of students reaches 97.22% which is included in the effective category. So that research on the development of interactive e-modules using a Project Based Learning (PjBL) learning model on automotive basics subjects in class X SMK N 2 Medan is declared valid, practical, and effective